The Role of Perceived Social Support in Reducing The Risk of PTSD Among COVID-19 Survivors in Indonesia - Haressa Lintang Rizkika; Nurlaela Widyarini; Panca Kursistin Handayani; Iffan Gallant El Muhammady (SS&H: Studies in Social Sciences and Humanities, 2024)
The COVID-19 pandemic has not only caused physical health concerns but has also led to psychological challenges, including the risk of post-traumatic stress disorder (PTSD). This study aimed to explore the relationship between perceived social support and PTSD in COVID-19 survivors. A sample of 221 participants was selected, and data were collected using modified Perceived Social Support and PTSD Checklist for DSM-V (PCL-5) scales. The results revealed a significant negative correlation (r = –0.356; p < 0.05) between perceived social support and PTSD, suggesting that higher social support is associated with lower PTSD symptoms. However, the findings are limited to the specific sample used, and future research should consider a more representative sample for broader generalization.